Cell-Free DNA Analysis of Targeted Genomic Regions in Maternal Plasma for Non-Invasive Prenatal Testing of Trisomy 21, Trisomy 18, Trisomy 13, and Fetal Sex. (6th January 2020) - Koumbaris, George; Kypri, Elena; Tsangaras, Kyriakos; Achilleos, Achilleas; Mina, Petros; Neofytou, Maria; Velissariou, Voula; Christopoulou, Georgia; Kallikas, Ioannis; González-Liñán, Alicia; Benusiene, Egle; Latos-Bielenska, Anna; et al.
Abstract: BACKGROUND: There is great need for the development of highly accurate cost effective technologies that could facilitate the widespread adoption of noninvasive prenatal testing (NIPT). METHODS: We developed an assay based on the targeted analysis of cell-free DNA for the detection of fetal aneuploidies of chromosomes 21, 18, and 13. This method enabled the capture and analysis of selected genomic regions of interest. An advanced fetal fraction estimation and aneuploidy determination algorithm was also developed. This assay allowed for accurate counting and assessment of chromosomal regions of interest. The analytical performance of the assay was evaluated in a blind study of 631 samples derived from pregnancies of at least 10 weeks of gestation that had also undergone invasive testing. RESULTS: Our blind study exhibited 100% diagnostic sensitivity and specificity and correctly classified 52/52 (95% CI, 93.2%–100%) cases of trisomy 21, 16/16 (95% CI, 79.4%–100%) cases of trisomy 18, 5/5 (95% CI, 47.8%–100%) cases of trisomy 13, and 538/538 (95% CI, 99.3%–100%) normal cases. The test also correctly identified fetal sex in all cases (95% CI, 99.4%–100%). One sample failed prespecified assay quality control criteria, and 19 samples were nonreportable because of low fetal fraction. CONCLUSIONS: The extent to which free fetal DNA testing can be applied as a universal screening tool for trisomy 21, 18, and 13 depends mainly on assay accuracy and cost. Cell-free DNA analysis of targeted genomic regions in maternal plasma enables accurate and cost-effective noninvasive fetal aneuploidy detection, which is critical for widespread adoption of NIPT.